2007
DOI: 10.1007/s11145-007-9094-6
|View full text |Cite
|
Sign up to set email alerts
|

Use orthography in L2 auditory word learning: Who benefits?

Abstract: The effect of capitalizing on orthography in auditory learning of English words was examined in 74 children who spoke Mandarin Chinese as their primary language. To use orthographic information for auditory word learning, children must recode printed words phonologically to assist the reconstruction of the speech single misheard or underspecified, an ability that may depend heavily on phonological awareness (PA). In this study, children with poorer PA of Chinese and those with better PA were taught novel Engli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 69 publications
(85 reference statements)
2
26
1
Order By: Relevance
“…Hu (2008) found that Chinese-speaking EFL students better associated a novel word's auditory form with its semantic referent when the word was presented in print form. The print effect was larger for the EFL students with better phonological awareness.…”
Section: Word Reading For Efl Studentsmentioning
confidence: 94%
“…Hu (2008) found that Chinese-speaking EFL students better associated a novel word's auditory form with its semantic referent when the word was presented in print form. The print effect was larger for the EFL students with better phonological awareness.…”
Section: Word Reading For Efl Studentsmentioning
confidence: 94%
“…Participants may have linked both the written and auditory FL word forms to the meaning representation accessed from the pictures during the letter-search task. Having had access to both written and auditory FL word forms may have facilitated learning (see Bird & Williams, 2002; Hu, 2008; Ricketts, Bishop, & Nation, 2009; Rosenthal & Ehri, 2008). In contrast, it is less clear to what extent FL auditory word forms were processed and how much they contributed to the learning effect.…”
mentioning
confidence: 99%
“…The only tentative benefit found for teaching approach was that learners with lower levels of English language literacy seemed to make more progress as they moved into secondary school and in relation to production if they had received French instruction with a stronger literacy focus at primary school. This indicates, perhaps, that such learners need access to the written form in order to facilitate retention of vocabulary and grammar forms, as suggested by Hu (2008) in relation to learners with lower levels of phonological awareness and by Harley and Swain (1984) commenting on the needs of young learners. It is possible that presenting language in an oral form only places a heavy burden on such learners, preventing them from retaining the language to which they are exposed or from recalling it easily.…”
Section: Literacy Versus Oracymentioning
confidence: 88%
“…Vocabulary development also potentially benefits from written input rather than oral input alone, according to a range of evidence reviewed by Hu (2008), who argues that a focus on orthographic forms helps to "'fossilize' the L2 speech signals" (p. 823) in the input, that is, it makes them more accessible and therefore more likely to be processed effectively. Beginning learners of a L2, especially those with weaker phonological awareness and, hence, poor speech perception, may find it hard to learn from oral input alone because they have difficulty in "constructing accurate, detailed phonological representations in the process of abstracting a stable specification of the sound structure of the new word from the input" (p. 825).…”
Section: Teaching Approach: Literacy and Oracymentioning
confidence: 99%